Examining the Potential of Art-Science Collaborations in the Anthropocene: A Case Study of Catching a Wave - Paterson, Shona K.; Le Tissier, Martin; Whyte, Hester; Robinson, Lisa B.; Thielking, Kristin; Ingram, Mrill; McCord, John (Frontiers in Marine Science, 2020)
There is a disconnect between ambition and achievement of the UN Agenda 2030 and associated Sustainable Development Goals that is especially apparent when it comes to ocean and coastal health. While scientific knowledge is critical to confront and resolve contradictions that reproduce unsustainable practices at the coast and to spark global societal change towards sustainability, it is not enough in itself to catalyse large scale behavioural change. People learn, understand and generate knowledge in different ways according to their experiences, perspectives, and culture, amongst others, which shape responses and willingness to alter behaviour. Historically, there has been a strong connection between art and science, both of which share a common goal to understand and describe the world around us as well as provide avenues for communication and enquiry. This connection provides a clear avenue for engaging multiple audiences at once, evoking emotion and intuition to trigger stronger motivations for change. There is an urgent need to rupture the engrained status-quo of disciplinary divisions across academia and society to generate transdisciplinary approaches to global environmental challenges. This paper describes the evolution of an art-science collaboration (Catching a Wave) designed to galvanise change in the Anthropocene era by creating discourse drivers for transformations that are more centred on society rather than the more traditional science-policy-practice nexus.